Mathematical aspects of computer and information sciences : 7th International Conference, MACIS 2017, Vienna, Austria, November 15-17, 2017, Proceedings /: 7th International Conference, MACIS 2017, Vienna, Austria, November 15-17, 2017, Proceedings. (2017) - Unknown
No abstract available